Analysis Quality Control In Rice Packing Projects To Reduce Defects Using Methods Statistical Quality Control (SQC) - Aziz, Muchammad Rif'an; Jufriyanto, Moh; Hidayat, Hidayat (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
The industry is growing rapidly, indirectly forcing business actors to pay attention to the quality of the goods they produce during the production process. Companies must maintain the quality of their products because quality affects how satisfied customers are with a product. PT. XYZ is a company engaged in steel construction and fabrication. The problems that often occur are defects such as Overlap welding defects, Porosity welding defects, and unavoidable Cutting process defects. This study aims to determine the level of damage, identify the factors that cause damage and recommend corrective actions. Statistical quality control methods are used to identify the causes of defects in the production process, with statistical tools including: check sheets, histograms, Pareto charts, Control Chart diagrams, and fishbone diagrams. The results showed that product damage or defects were within reasonable limits but corrective action was needed to reduce defects. It can be seen from the Pareto diagram that the Overlap welding defects are 37.5% more than all product defects. Proposed improvements that need to be implemented by the company are cleaning the material before welding, performing treatment on the welding wire according to the Quality Control department's recommendations, checking the machine's stability before use and carrying out machine maintenance once a week.